Complete Elimination of Peripheral Auditory Input Before Onset of Hearing Causes Long-Lasting Impaired Social Memory in Mice - Guo, Rui; Li, Yang; Liu, Jiao; Gong, Shusheng; Liu, Ke (Frontiers in Neuroscience, 2021)
Hearing is one of the most important senses needed for survival, and its loss is an independent risk factor for dementia. Hearing loss (HL) can lead to communication difficulties, social isolation, and cognitive dysfunction. The hippocampus is a critical brain region which greatly involved in the formation of learning and memory, and is critical not only for declarative memory, but also for social memory. However, until today, whether HL can affect learning and memory is poorly understood. This study aimed to identify the relationship between HL and hippocampal-associated cognitive function. Mice with complete auditory input elimination before the onset of hearing were used as the animal model. They were first examined via auditory brainstem response (ABR) to confirm hearing elimination, and behavior estimations were applied to detect social memory capacity. We found significant impairment of social memory in the mice with HL compared to the controls (P < 0.05); however, no significant differences were seen in the tests of novel object recognition, Morris water maze, and locomotion in the open field (P > 0.05). Therefore, our study firstly demonstrates that hearing input is required for the formation of social memory, and hearing stimuli play an important role in the development of normal cognitive ability.